MANAJEMEN OTONOMI DAERAH - Soleha, Lilis Karnita (Majalah Bisnis & IPTEK, 2021)
Regional Autonomy opens great hopes for communities and local government, especially the feel for these aspirations are locked by a uniform pattern adopted pemrintah center. Regional autonomy make diversity, and local government and the community can take the best decisions for the region. But such expectations would be raw if it is not accompanied by changes in attitudes and paradigms. Dependence and helplessness facing the center, has created paradigam and mental attitude of certain patterns, which must be changed along with the flexibility to be more independent. Keywords: regional autonomy; management